A study on the emergence of sound-sign correspondence in Italian-speaking 5-year-old pre-schoolers - Bigozzi, Lucia; Incognito, Oriana; Mercugliano, Alice; De Bernart, Diletta; Botarelli, Lucia; Vettori, Giulia (Frontiers in Education, 2023)
This study investigates the emergence of sound-sign correspondence in Italian-speaking pre-schoolers of 5 years old. There are few experimental studies on the precursors of reading and writing skills and those existing mainly focus on letter knowledge or logographic processing of words in pre-schoolers. This paper evaluates and compares 5-year-old children’s use of the logographic processing or the use of sound-sign processing to decode target words in original and modified versions. Furthermore, we verify whether pre-schoolers’ type of reading words (logographic versus sound-sign processing) vary in accordance with children’s socio-cultural differences (i.e. type of school and socio-cultural information from parents). This study tested 94 children (M-age = 5 years and 8 months) at the end of the last year of preschool. Six stimulus logos were used to evaluate children’s ability to decode words and the type of decoding (logographic or sound-sign processing). The Chi-square results confirm that the achievement of the correspondence between sound-sign at the base of reading and writing has already started in preschool. Our findings shed light on a significant proportion of pre-schoolers who can already read words via sound-sign processing or show the emergence of notational awareness, while the others still rely on logographic processing. Moreover, the results show that pre-schoolers’ notational awareness is related to socio-cultural characteristics pertaining to schools and families. These findings suggest that 5 years is an important age for the disentanglement between logographic and sound-sign correspondence in pre-schoolers and provide useful implications for theory and practice.